Illustrator CS5 bible - Alspach, Ted (Wiley Pub., 2010)
"ILOR is a powerful tool with the potential to intimidate, but in this comprehensive guide Adobe product manger Ted Alspach reveals the secrets so you can harness the amazing power of ILOR. This edition includes coverage on all the new features. Part I covers ILOR Basics which introduces readers to the ILOR interface and the ABCs of working with ILOR documents. Part 2, Putting ILOR to Work, shows readers how to manipulate type, distort artwork, and apply strokes and fills. Part 3 titled Mastering ILOR, explains transparency, how to work in 3D and how to use styles, effects, and filters. Finally, Part 4 shows readers how to output their work"--Resource description page.